Blue Economy and Economic Growth: The Sulawesi Economic Corridor Policy for Accelerated Development - Marjani; Hasddin; Mirad; Asrul; Murini (Journal of Indonesian Scholars for Social Research, 2025)
The blue economy is a crucial national development priority aimed at reinforcing Indonesia’s position as a leading maritime nation. The fisheries and marine sectors have significantly contributed to national economic growth, yet challenges such as marine environmental degradation persist. Eastern Indonesia, home to nearly 50% of the country’s mining reserves, has been designated as a hub for national mining activities. However, empirical evidence suggests that mining operations negatively impact marine sustainability, necessitating an economic policy framework that balances development with environmental conservation. The blue economy approach offers a viable solution by integrating fisheries, maritime, and mining sectors to foster inclusive and resilient growth. This study explores a balanced blue economy model that aligns economic development with sustainability goals. Given the impending conclusion of the Sulawesi Economic Corridor acceleration framework in 2025, the study’s findings can guide future development planning. To accelerate sustainable economic growth in Eastern Indonesia, four strategic agendas are proposed. First, develop a comprehensive database to assess economic achievements, potential opportunities, and existing challenges in the blue economy. Second, evaluate the resources, performance, and economic contribution of the mining and oil and gas sector at national and regional levels. Third, analyze intersectoral relationships within the blue economy to formulate effective growth strategies. Lastly, design a sustainable blue economy model that integrates fisheries, maritime, and mining sectors, ensuring inclusive and long-term development. Through these strategies, Eastern Indonesia can achieve sustainable economic progress while safeguarding its marine resources.